Description of immatures and natural history of the weevil Loncophorus pustulatus (Champion, 1903) (Coleoptera: Curculionidae: Curculioninae) associated with flowers of Ceiba speciosa (A. St.-Hil.) Ravenna (Bombacoidea: Malvaceae) in southeast Brazil - Vanin, Sergio Antonio; Bená, Daniela De Cassia; Albertoni, Fabiano Fabian (Zootaxa, 2013)
Larva and pupa of Loncophorus pustulatus (Champion, 1903) (Curculionidae: Curculioninae: Anthonomini) are de-scribed, illustrated and compared with descriptions of immatures of two other species of Loncophorus. Weevil larvae were found inside aborted flowers on the ground under Ceiba speciosa (A. St.-Hil.) Ravenna (Malvaceae), in the city of São Paulo, State of São Paulo, and reared to adults in laboratory. Data obtained in the field and under laboratory conditions are presented. Parasitoidism of weevil larvae by wasps of the genus Catolaccus (Hymenoptera: Pteromalidae) is reported.